The Influence Of Growth Disorders In Stunting Children On Development - Zuhrufa Wanna Yolanda; Iskandar . (Lambung Mangkurat University, 2023)
Indonesia is one of the countries in the Asian region with a high prevalence of stunting, which if not addressed can lead to long-term consequences, namely health, development and economic problems. This study aims to provide information about the effect of stunting on child development. Research methods use literature review with narrative review. Research articles/data were obtained through Google Scholar, Pubmed, The Garba Rujukan Digital (Garuda) and DOAJ. The keywords used are stunting, child growth, growth and development, growth disorders, child development, risk factors and the impact of stunting. Some literature states that stunting can affect children's development. The impact on development is both short-term and long-term. In addition, the causes and risk factors for stunting are numerous and multifactor so that stunting must be addressed immediately and the literature related to stunting will add information and knowledge in overcoming stunting cases.